2014
DOI: 10.1158/1055-9965.epi-13-1163
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Randomized Trial of the Effects of Exercise Dose and Type on Psychosocial Distress in Breast Cancer Patients Undergoing Chemotherapy

Abstract: Background: Exercise may improve psychosocial distress in patients with cancer; however, few studies have examined the effects of different types or doses of exercise, or whether exercise effects are related to baseline depression levels.Methods: In a multicenter trial in Canada, we randomized 301 patients with breast cancer initiating chemotherapy to thrice weekly, supervised exercise consisting of either a standard dose of 25 to 30 minutes of aerobic exercise (STAN; n ¼ 96), a higher dose of 50 to 60 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 29 publications
(33 reference statements)
2
34
0
2
Order By: Relevance
“…10 BDI total scores range from 0 to 63 and are subdivided into "minimal" (0-13), "mild" (14)(15)(16)(17)(18)(19), "moderate" (20)(21)(22)(23)(24)(25)(26)(27)(28), and "severe" (29-63) depression. Baseline psychiatric history and drug use history were assessed using the MINI International Neuropsychiatric Interview, 11 a clinician-administered structured interview based on DSM-IV criteria for psychiatric disorders, and baseline medical history was assessed with a free-form medical history questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…10 BDI total scores range from 0 to 63 and are subdivided into "minimal" (0-13), "mild" (14)(15)(16)(17)(18)(19), "moderate" (20)(21)(22)(23)(24)(25)(26)(27)(28), and "severe" (29-63) depression. Baseline psychiatric history and drug use history were assessed using the MINI International Neuropsychiatric Interview, 11 a clinician-administered structured interview based on DSM-IV criteria for psychiatric disorders, and baseline medical history was assessed with a free-form medical history questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…A considerable body of literature has shown that participation in physical activity may improve QoL outcomes in cancer survivors . For example, meta‐analyses have provided consistent evidence of medium to large effects of physical activity on reduced fatigue in BCS .…”
Section: Introductionmentioning
confidence: 99%
“…The secondary aim was to determine moderators of BEAT Cancer compared to UC on the aforementioned outcomes. Demographic (age, income, marital status) and medical (cancer stage, months since diagnosis, cancer treatment) were chosen based on plausibility and literature review [6, 8, 10-12, 20, 27, 29]. …”
Section: Introductionmentioning
confidence: 99%